THE CORRELATION BETWEEN SELF-CONFIDENCE AND SPEAKING ABILITY OF THE SECOND YEAR STUDENTS OF ENGLISH STUDY PROGRAM OF UNIVERSITAS RIAU - Anggraini, Paramitha; Marzuki, Marzuki; Dahnilsyah, Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to find out the correlation between self-confidence and speaking ability of the second year students of English Study Program of Universitas Riau. The correlational research was used to find out the relationship between two variables. To collect the data in this research were speaking test and questionnaire. A cluster random sampling technique is used to determine the sample of the research. There were 34 students participating in this research. Oral performance was used to know the students' speaking ability and questionnaire was used to know students’ self-confidence. The result of the study shows that there was a correlation between two variables. The value of correlation coefficient was 0.349. it was on scale 0.20 – 0.399 it meant that the correlation between self-confidence and speaking ability of the second year students of English Study Program of Universitas Riau categorized as low correlation. In other words, there is other factors can influence students’ speaking ability. The finding could important distributions to both understand, self-confidence and speaking ability especially the relationship between the two variables.Key Words: Correlation, Self-Confidence, Speaking Ability